Hip abductors and thigh muscles strength ratios and their relation to electromyography amplitude during split squat and walking lunge exercises - Petr Stastny; James J. Tufano; Michal Lehnert; Artur Golas; Amr Zaatar; Zuzana Xaverova; Adam Maszczyk (Palacký University Olomouc, 2015)
Background: The hip abductors (HAB), quadriceps (Q) and hamstrings (H) reciprocal strength ratios are predictors of electromyography (EMG) amplitude during load carrying walking at moderate intensity. Therefore, these strength ratios might predict also the EMG during the exercises as walking lunge (WL) or split squat (SSq) at submaximal intensity. Objective: To determine whether the EMG amplitude of vastus mediali (VM), vastus laterali (VL), biceps femoris (BF) and gluteus medius (Gmed) is associated with muscle strength ratio during SSqs and WLs. To determine whether the EMG amplitude differs between individuals with HAB/H ratio above and below one and between individuals with H/Q or HAB/Q ratio above and below 0.5 during SSqs and WLs. Methods: 17 resistance-trained men (age 29.6 ± 4.6 years) with at least 3 years of strength training performed in cross-sectional design 5 s maximal voluntary isometric contractions (MVIC) on an isokinetic dynamometer for knee extension, knee flexion, and hip abduction. The MVIC was used to normalize the EMG signal and estimate the individual strength ratios. Than participants performed WL and SSq for a 5 repetition maximum, to find out muscle activity at submaximal intensity of exercise. Results: The H/Q ratio was associated by Kendall's tau (τ) with VM (τ = .33) and BF (τ = -.71) amplitude, HAB/Q ratio was associated with BF (τ = -.43) and Gmed (τ = .38) amplitude, as well as HAB/H was associated with VM (τ = -.41) and Gmed (τ = .74) amplitude. ANOVA results showed significant differences between SSq and WL (F(4, 79) = 10, p < .001, ηp2 = .34) in Gmed amplitude, where WL resulted in higher Gmed amplitude compared to SSq. Other significant differences were found between H/Q groups (F(4, 29) = 3, p = .04, ηp2 = .28) in VM and Gmed amplitude, where group with H/Q > 0.5 showed higher VMO amplitude and lower Gmed amplitude. Furthermore, significant difference was found for HAB/H groups (F(4, 29) = 4, p = .02, ηp2 = .34) in VM amplitude, where group with HAB/H < 1 showed higher VM amplitude. Conclusions: The ratios of HAB, H and Q are able to predict Gmed, VM and BF activity during WL and SSq. WL resulted in higher activity level of Gmed than SSq, because WL includes the impact forces as part of lunge movement. WL should be used in resistance-training programme, if the strengthening of Gmed or VM is the aim.